STEM Student Learning across Countries - Loyalka, Prashant; Liu, Ou Lydia; Chirikov, Igor (International Higher Education, 2021)
Universities contribute to economic growth and national competitiveness by equipping students with higher-order thinking and academic skills. Despite large investments in university STEM education, little is known about how the skills of STEM undergraduates compare across countries and by institutional selectivity. The authors have provided direct evidence on these issues by collecting and analyzing longitudinal data on tens of thousands of computer science and electrical engineering students in China, India, Russia, and the United States.